2013
DOI: 10.1007/s12013-013-9621-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Activity in the Ubiquitin–Proteasome System: From Large Scale Discoveries to Single Cells Analysis

Abstract: The ubiquitin proteasome system (UPS) is the primary pathway responsible for the recognition and degradation of misfolded, damaged, or tightly regulated proteins in addition to performing essential roles in DNA repair, cell cycle regulation, cell migration, and the immune response. While traditional biochemical techniques have proven useful in the identification of key proteins involved in this pathway, the implementation of novel reporters responsible for measuring enzymatic activity of the UPS have provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…11 One limitation of peptide-based reporters is their rapid degradation by intracellular peptidases and proteases. Designing fluorescent peptide-based reporters that report the activity of the UPS by the detection of proteasome-mediated reporter degradation 2 can be challenging. Often, a significant amount of the reporter is degraded by cytosolic proteases before the activity of the UPS can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…11 One limitation of peptide-based reporters is their rapid degradation by intracellular peptidases and proteases. Designing fluorescent peptide-based reporters that report the activity of the UPS by the detection of proteasome-mediated reporter degradation 2 can be challenging. Often, a significant amount of the reporter is degraded by cytosolic proteases before the activity of the UPS can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…UPP is an important mechanism in the degradation of proteins (18,19), which has not been reported in previous studies of TRAIL-resistance mechanism in myeloma cells. Recent studies showed that the disorder of tumor cell regulatory function can be due to the inactivation of key regulators.…”
Section: Discussionmentioning
confidence: 72%
“…The ubiquitin-proteasome system (UPS) is the primary pathway responsible for the recognition and degradation of misfolded, damaged, and tightly regulated proteins. It also plays crucial roles in DNA repair, cell cycle regulation, cell migration, and the immune response (Melvin et al, 2013). Ubiquitin (Ub) is a small protein composed of 76 amino acids that is highly conserved in eukaryotes (Tomohiro and Mizuno, 1995).…”
Section: Expression Of Herc4 In Lung Cancer and Its Correlation With mentioning
confidence: 99%